2020
DOI: 10.3390/catal10010121
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic and Catalytic Performance of Co and Co-Mo Metal Impregnated in Sarulla Natural Zeolite Catalyst for Hydrocracking of MEFA Rubber Seed Oil into Biogasoline Fraction

Abstract: This research was aimed to investigate the effect of Co and Co-Mo metal loaded on Sarulla Natural Zeolite which has been activated and calcined (SNZ-Cal) as supports for better understanding of characterization and catalytic activity on hydrocracking of MEFA rubber seed oil. The Co and Co-Mo metal was added through a wet impregnation method using Co(NO3)2·6H2O and (NH4)·6Mo7O24·4H2O precursor salts. The catalyst was oxidized at 500 °C for 2 h within oxygen gas flow, followed by a reduction process with H2 gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 25 publications
(22 reference statements)
1
17
0
Order By: Relevance
“…The initial preparation of natural zeolite followed the procedure carried out by Sihombing et al [13]. Natural zeolite was crushed and sieved with a 100 meshsieve.…”
Section: Zeolite Preparation and Activationmentioning
confidence: 99%
“…The initial preparation of natural zeolite followed the procedure carried out by Sihombing et al [13]. Natural zeolite was crushed and sieved with a 100 meshsieve.…”
Section: Zeolite Preparation and Activationmentioning
confidence: 99%
“…The preparation and activation of natural zeolite in this study followed the procedure reported by Sihombing et al [26] In the early stages, natural zeolite was crushed and sieved to obtain zeolite with a size of 100 mesh. This natural zeolite was then washed by soaking in distilled water for 24 hours at room temperature.…”
Section: Preparation and Activation Of Natural Zeolitementioning
confidence: 99%
“…Adsorption-desorption isotherm graph of ANZ, ZB 0.2 M, ZB 0.5 M and ZB 2 M can be seen in Figure 3. Based on adsorption-desorption isotherm in Figure 3, the pattern in the diagram is categorized into Type IV with the presence of hysteresis loop and high rises in the graph at P/Po (Sihombing et al, 2020;Sihombing et al, 2018;Hasanuddin and Rahmat 2015;Fathi et al, 2014). Moreover, the graph shows that the rate of adsorption is not the same as the desorption rate.…”
Section: Xrf Analysismentioning
confidence: 99%
“…Natural Zeolite (NZ) is usually formed as a secondary mineral in several geological activities in the Earth's crust. Indonesia has got many sources of natural zeolite which are widely spread across various regions such as Lampung (Elysabeth et al, 2019), Bayah (Hartono et al, 2019), Tasikmalaya (Dewi et al, 2016), Ende-Flores (Noelaka et al, 2018), Malang (Erlynata et al, 2014), Gunung Kidul (Hernawan et al, 2015) as well as in Sarulla -North Tapanuli (Sihombing et al, 2020). NZ is available in large quantities at low-cost exploitation and until today, it has not been fully utilized.…”
Section: Introductionmentioning
confidence: 99%